Evidence of a sex-dependent restrictive epigenome in schizophrenia. (June 2015) - Chase, Kayla A.; Rosen, Cherise; Rubin, Leah H.; Feiner, Benjamin; Bodapati, Anjuli S.; Gin, Hannah; Hu, Edward; Sharma, Rajiv P.
Abstract: When compared to women, men have a higher incidence of schizophrenia, with increases in negative and cognitive symptoms, and an overall poorer disease course. Schizophrenia is conceptualized as a disorder of aberrant gene transcription and regulation. Thus, epigenetics, the study of environmentally induced changes in gene regulation, could advance our understanding of the molecular underpinnings of schizophrenia. Peripheral histone methyltransferase (HMT) mRNA levels have been previously shown to be significantly increased in patients with schizophrenia and correlate with symptomology. In this independent study, peripheral lymphocytes were extracted and clinical symptoms were measured on 74 participants, (40 patients with schizophrenia (19 women, 21 men) and 34 healthy individuals (19 women, 15 men)). HMT (G9α, SETDB1 and GLP) mRNA levels and their resulting histone modification H3K9me2 were measured with RT-PCR and ELISA respectively. Plasma estradiol levels were also measured via ELISA and correlated with HMT mRNA. Clinical symptoms were measured utilizing the Positive and Negative Syndrome Scale (PANSS) and the Heinrichs Carpenter Quality of Life Scale (QLS). The results indicate that men with schizophrenia expressed the highest levels of G9α, SETDB1 mRNA and H3K9me2 protein levels. Additionally, higher levels of symptom presentation and an overall poorer quality of life were correlated with higher HMT mRNA and H3K9me2 protein levels in a sex-dependent pattern. These data support the hypothesis of a sex-dependent restrictive epigenome contributing towards the etiology of schizophrenia. The histone methyltransferases measured here could be potential future therapeutic targets for small molecule pharmacology. Highlights: Peripheral samples were used for study procedures, including lymphocyte mRNA and H3K9me2 levels and plasma estradiol levels. Men with schizophrenia expressed higher HMT mRNA and H3K9me2 levels compared to controls and females with schizophrenia. Histone methyltransferase mRNA levels correlated with plasma estradiol levels. Elevated HMT mRNA and H3K9me2 levels correlated with worse symptoms and quality of life in a sex-dependent pattern. The results suggest that a sex-dependent restrictive epigenome may underlie the etiology of schizophrenia.